PENGARUH PENDAPATAN ASLI DAERAH TERHADAP BELANJA MODAL PADA KABUPATEN DAN KOTA PROPINSI SULAWESI UTARA - Lengkong, Justonly; Saerang, David P.E.; Alexander, Stanly (GOING CONCERN : JURNAL RISET AKUNTANSI, 2013)
Regional Original Income is the main source of income of the local region itself. Regional Original Income is expected to be able to support Expense of Capital, because the Regional Original Income will increase is expected to add more revenue from existing infrasturcture development. This research aimed to determine the effect of Regional Original Income for Expense of Capital. Variables used in this research Is the Regional Original Income and Expense of Capital. The research data in the form of quantitative data and a secondary data obtained from the Central Board of Statistic in North Sulawesi. In this research has used simple regression method assisted by classical assumption. This research showed that the Regional Original Income has no effect on Expense of Capital.